Композит MIL-100(Fe)/диатомит для фотокаталитического разложения фенола - Мацкан, Полина Андреевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Two MIL-100(Fe)/diatomite composites (with a surface area of 441 and 322 m2/g and pore volume of 0.31 and 0.21 cm3/g respectively) were synthesized by the assembly of MIL-100(Fe) metal-organic frameworks inside wide pores of diatomite. It was shown that synthesized composites are characterized with hierarchical pore structure. The study of adsorption and catalytic activity showed that the samples can be used as adsorbents for removal of volatile organic compounds from air and catalysts in the Fenton reaction for deep oxidation of aromatic compounds.